Studi Konsentrasi Pada Bauksit Asal Tayan Dengan Menggunakan Metode Flotasi Kebalikan - Christin Palit; Suliestyah suliestyah (Jurnal Geomine, 2020)
This paper is one of a study that implements reverse flotation methods as an alternative beneficiation on bauxite processing. This study is aimed to increase alumina content in bauxite so its qualified as feed of Bayer Process (Al2O3 51%, SiO2 7%, Al2O3 / SiO2 10 ratio). The experiments was focused to increase alumina content from bauxite were carried out in a 1375 mL of flotation cell tank. Dodecylamine (DDA) was used as the collector, starch as the depressant, and Dowfroth 1012 as frother. The overall experiments were conducted on solid content to solution 25% w/w and speed rotation of impeller were 900 rpm. The characterization results showed that the feed ore had Al2O3 and SiO2 content, respectively 61,24% and 27,9%. Experiments were carried out in several variations to determine what variables were most affected in the study. There were 4 variations used in this study, size fraction of particle, collector dosage, pH of slurry and with the addition of / without the addition of depressants. Alumina content as results of flotation was analyzed by XRF. The results of XRF of flotation products show that increasing of alumina content. The optimum pH range of bauxite flotation using DDA as collectors can be achieved at pH 4 – 10. From the results, The increasing of collector dosage at pH 10 gives a good result on Al2O3 content is 62% with 50,44% recovery of Al2O3 obtained at dosage of collector at 500 g/ton. The Al2O3 content which higher in conditions without the addition of depressant is 66,8%. While for the size fraction variation, it shows that separation better in the finer particle which gives an increasing of alumina and decreasing of silica as a result. The best condition in this study were achieved by 400 g/ton of DDA dosage, 400 g/ton of depressant dosage and size fraction of particle in -325 mesh at pH 10 with increasing alumina to 79.1%.